Azathioprine Maintenance Therapy to Prevent Relapses in Autoimmune Pancreatitis. Issue 4 (April 2017) - de Pretis, Nicolò; Amodio, Antonio; Bernardoni, Laura; Campagnola, Pietro; Capuano, Fabiana; Chari, Suresh T; Crinò, Stefano; Gabbrielli, Armando; Massella, Arianna; Topazian, Mark; Frulloni, Luca
Abstract : OBJECTIVES: : Steroids are used to induce remission in autoimmune pancreatitis (AIP). Low‐dosage steroid therapy or immunosuppressant (IMs) has been proposed as maintenance therapy to prevent AIP relapse. Few and conflicting data have been published on the efficacy of azathioprine (AZA) in preventing AIP relapse. The aim of this study was to evaluate the indication and efficacy of AZA as maintenance therapy to prevent disease relapse in AIP. METHODS: : Patients suffering from AIP diagnosed according to the ICDC in type 1, type 2, and not otherwise specified (NOS) were divided in those treated with AZA (AZA + group) as maintenance therapy and not treated with maintenance therapy (AZA − group). Exclusion criteria were: previous pancreatic surgery, other autoimmune diseases as indication for AZA treatment, and use of IMs different from AZA. Drug safety, clinical and instrumental outcome of AZA + patients were evaluated. RESULTS: : A total of 23 patients (18 Males and 5 Females, mean age 54±11 years) in AZA + group and 97 (58 Males and 39 Females, mean age 45±18 years) in AZA − group were compared. In AZA + group, patients were significantly older ( P =0.043), type 1 AIP was more frequently diagnosed (87 vs. 51%, P =0.006), sIgG4 higher (758±625 vs. 311±409 mg/dl, P <0.001), other organ involvement (OOI) more frequently observed (83 vs. 48%, P =0.002), with higher frequency of relapse before AZA treatment (78 vs. 14%, P <0.001). Three patients in AZA + group required drug discontinuation because of adverse events. Twenty patients were therefore evaluated for outcome. Six out of 20 patients (30%) relapsed after 24±15 months (5 in pancreas and 1 on biliary tract). They were retreated with steroids and continued AZA. Two out of 6 patients (33%) had a second relapse, after respectively 11 months (in pancreas and kidney) and 22 months (in kidney). CONCLUSIONS: : AZA is an effective and safe treatment to prevent AIP relapses.